Environmental Interface Chemistry and Pollution Control (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This is a reprint of the Special Issue titled "Environmental Interface Chemistry and Pollution Control" that was published in Sustainability. The scope of this Special Issue covers research on environmental interface chemistry, pollution control, and environmental materials. In view of the published contributions, it is a collection of related research that mainly provides new insights into the resource utilization of solid waste and water quality evaluation. The research presented in this collection will offer an important reference for further exploration.